2017
DOI: 10.1590/0001-3765201720160697
|View full text |Cite
|
Sign up to set email alerts
|

Active caspase-3 expression levels as bioindicator of individual radiosensitivity

Abstract: Several molecules and events involved in cell response to radiation-induced damage have been investigated towards a personalized radiotherapy. Considering the importance of active caspase-3 in the proteolytic cascade that ensures radiation-induced apoptosis execution, this research was designed to evaluate the expression levels of this protein as a bioindicator of individual radiosensitivity. Peripheral blood samples of 10 healthy individuals were gamma-irradiated (cobalt-60 source) with 1, 2 and 4 Gy (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…f) which is critical in carrying out apoptosis. An increased level of caspase‐3 can serve a bio‐indicator of radiosensitivity . VCN‐2 in combination with radiation also resulted in an increase in the BECN‐1 mRNA levels (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…f) which is critical in carrying out apoptosis. An increased level of caspase‐3 can serve a bio‐indicator of radiosensitivity . VCN‐2 in combination with radiation also resulted in an increase in the BECN‐1 mRNA levels (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Among the 16 downregulated proteins, caspase 3 was the most downregulated in the RT-R-MDA-MB-231 cells, which is suggested as one of the mechanisms for RT resistance [ 20 ]. Figure 1 A shows a graphical representation of the proteins concerning the fold change.…”
Section: Resultsmentioning
confidence: 99%
“…caspase‐3 is a significant protease in the cascade reaction, and is therefore known as the 'hallmark enzyme' of cell apoptosis . Considering the importance of active caspase‐3 in the proteolytic cascade that ensures radiation‐induced apoptosis execution . To investigate the possible role of radiation‐induced heart disease, we examined the cleaved caspase‐3 and cyclophilin A expression levels in the heart of irradiated rats and found that, 6 Gy gamma irradiation induces a marked elevation in the former parameters compared with the corresponding normal values.…”
Section: Discussionmentioning
confidence: 99%